Do stakeholders matter in strategic decision making of a sports organization? - Miragaia, D. A. M. (2020)
This study aims to identify and prioritize the stakeholders involved in making decisions in a sports organization. A multiple linear regression analysis was used to assess the influence of the attributes of power, legitimacy and urgency on the salience of the various stakeholders. The results showed a convergence of external and internal decision makers’ perceptions, concerning the three main stakeholder groups: top management, sponsors and member association. Pearson correlations identified four types of stakeholder: definitive, dangerous, demanding and non-stakeholders. A generalized differentiation was also found in stakeholder classification, regarding evaluation of attributes, between external and internal decision makers. In addition, the study suggests the success of organizations’ management will depend on correct identification of stakeholders and consequent assessment of their relevance, in order to highlight who should get priority, and how, in strategic decision making.